Site-selectivity of symbiotic (parasitic?) pits in crinoid column material from the middle Silurian (Wenlock: Sheinwoodian) of western Estonia. Issue 2 (14th November 2022) - Thomka, James R.; Vinn, Olev; Toom, Ursula
Abstract: Crinoid specimens containing symbiotic (potentially parasitic) pits are relatively rare in Silurian strata of Estonia. The first specimen of middle Silurian-age (Wenlock: Sheinwoodian) crinoid material containing such pits—a pluricolumnal of uncertain affinity—was recently reported from the Jaagarahu Formation of Saaremaa Island. The presence and morphology of pits were previously described, but a noteworthy paleoecological phenomenon that was not initially documented involves the site-specificity of pit occurrence along the pluricolumnal. All 21 of the pits distributed around the lateral circumference of the specimen are located on plate sutures, demonstrating a degree of site-selectivity that contrasts strongly with the more random distribution of pits observed in most Silurian crinoid assemblages. The underlying paleoecological driver of this site-selectivity remains enigmatic, particularly considering some reports that suggest a preference for the latera rather than the sutures of Paleozoic crinoid columns.